The Learnability of Cognitive and Metacognitive Reading Strategies in Moroccan Higher Education: A Quasi-experimental Study - Msaddek, Mohammed (Journal of Education and Training, 2023)
Constituting a substantive part of my unpublished Doctoral Dissertation that was defended in 2015, the present study probes into the impact of (meta) cognitive reading strategy training on Moroccan EFL students’ strategic processing of textual content. In principle, it draws parallels between the (meta) cognitive strategic act implemented by the English department first-semester university learners (Control group: N=50; Experimental group: N=63) before the metacognitive strategy intervention and the one enacted by these two targeted groups after the intervention. To put to the test this straightforwardly stated assumption, such research instruments as reading comprehension texts, reading strategy training, and retrospective questionnaire were resorted to for eliciting the relevant data. The results reveal that the delivery of explicit (meta) cognitive strategy training is deemed a contributive factor in culminating in improved (meta) cognitive strategy application among the treatment group. Thus, a panoply of recommendations that are germane to education and research as well as a range of limitations which confronted the current research study are tacitly put forth.